Analysis of the problem of Macedonian folk dance recognition - Martinovikj, Darko; Mihova, Marija; Jovanov, Mile (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2013)
Human experts in dancing and even the enthusiasts can easily conclude if someone is following the sequence of movements of a dance according to the music. But, if the task is given to the computer, it wouldn’t be an easy task, because the computer can only understand and work with numbers. In this paper we analyse the existing solutions for dance recognition and expand the idea toward building a system for dance recognition of traditional Macedonian folk dances. Different approaches for the used hardware, algorithms and methods are described and compared with Macedonian folk dance characteristics.
Keywords: Macedonian folk dance characteristics, Dance Recognition, Kinect sensor, gesture Recognition